2022
DOI: 10.1002/jmv.27768
|View full text |Cite
|
Sign up to set email alerts
|

Remdesivir treatment in hospitalized patients affected by COVID‐19 pneumonia: A case‐control study

Abstract: To date the optimal antiviral treatment against severe coronavirus disease 2019 (COVID‐19) has not been proven; remdesivir is a promising drug with in vitro activity against several viruses, but in COVID‐19 the clinical results are currently not definitive. In this retrospective observational study, we analyzed the clinical outcomes (survival analysis, efficacy, and safety) in a group of hospitalized patients with COVID‐19 treated with remdesivir in comparison with a control group of patients treated with othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The nucleoside analog is incorporated into the generating RNA strand and evades proofreading to successfully inhibit viral RNA synthesis. Several clinical trials and a recent case-control study demonstrated reduced time to recovery, hospitalization time, morbidity, and mortality ( 8 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…The nucleoside analog is incorporated into the generating RNA strand and evades proofreading to successfully inhibit viral RNA synthesis. Several clinical trials and a recent case-control study demonstrated reduced time to recovery, hospitalization time, morbidity, and mortality ( 8 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, some antiviral drugs used in various studies have shown significant effects, such as reducing viral load, improving overall condition, and reducing hospitalization time. Generally, antiviral treatment should be initiated as early as possible to reduce viral replication and improve patient prognosis [20,22,21].…”
Section: Resultsmentioning
confidence: 99%
“…Boglione et al. found that treatment with remdesivir was associated with a lower rate of mortality and intensive care unit (ICU) admission and a shorter time of hospitalization in a case-control study [ 120 ]. Marrone et al.…”
Section: Effects Of Medications On Viral Infection-induced Inflammationmentioning
confidence: 99%